Peer Education sebagai Upaya Pencegahan HIV/AIDS - Safitri Safitri (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
Adolescents are at the center of HIV/AIDS endemic worldwide, about 50 % of all new cases of HIV occur in youth between age 15 and 24 years. In Indonesia, based on the directorate general of P2P the number of HIV positive cases from year to year tends to increase and in 2018 it was reported as many as 46,659 cases. Likewise, the Jambi city, based on data from the health department, the number of cases of HIV / AIDS in adolescents was found in 24 cases (2017) and 13 cases (2018). Peer education is considered a core pillar of HIV prevention efforts in general and has been proven effective in increasing knowledge and promoting changes in attitudes and behavior. Target outcomes expected are: there is an increased knowledge between before and after peer education. This community service was carried out in November 2019 at SMA N 8 Jambi City. The target of this activity is students at SMA Negeri 8. The method used is peer education. The results of dedication are an increase in HIV/AIDS knowledge to bring positive changes in the sexual behavior of school adolescents and prevent them from the HIV/AIDS epidemic